Call for Papers : The Impact of Black Lives Matter Movement in the Era of COVID-19 Pandemic - International Journal of Community Development & Management Studies (IJCDMS) (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)
Number of pages: 15

Semaji - Black Community Resource Centre (BCRC) (2020)
Number of pages: 25

Semaji - Black Community Resource Centre (BCRC) (2020)
Number of pages: 15

Semaji - Black Community Resource Centre (BCRC) (2020)
Number of pages: 12

Semaji - Black Community Resource Centre (BCRC) (2020)
Number of pages: 18

Black in Quebec : Progress Report - Davids, John; Fang, Xiaoyan (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)
Number of pages: 30

Redefining the Black Experience in Montreal: One Institution at a Time - The Project Woke Interns (Black Community Resource Centre (BCRC), 2020)
Project Woke interns identified and investigated three critical themes affecting the Black community in Montreal. An analysis of societal issues and Canada’s Anti-Racism Strategy Project revealed harmful anti-human rights gaps affecting the Black Community. The findings from several consultations further validated these gaps. A comprehensive list of recommendations is included along with next steps as a continuation to advance Black human rights in Montreal, and elsewhere, along with the support of government and non-government actors.

A Posthumous Honour for a Conspicuous Life : Dr. Gaspard in Quebec - Williams, Dorothy (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
This story is an attempt to understand an unknown individual whose life was significant but has now been forgotten. He was American-born, yet his mother tongue was French. He served Canada in French units but embraced the English-speaking Black community once in Montreal. His life speaks of a complexity of language not often explored in narratives of Quebec’s English-speaking community, particularly in those histories about Blacks in the province. I trust this will be the beginning.
Parallel title: QUESCREN Working Paper no.3

Hommage posthume à une existence remarquable : L'oeuvre du docteur Gaspard au Québec - Williams, Dorothy (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
Parallel title: Document de travail QUESCREN no.3

Semaji - Black Community Resource Centre (BCRC) (2020)
Number of pages: 15

Semaji - Black Community Resource Centre (BCRC) (2020)
Number of pages: 16

Semaji - Black Community Resource Centre (BCRC) (2020)
Number of pages: 9

Activity Report 2019-2020 - Jamaica Association of Montreal (JAM) (2020)
The Association was founded in November 1962, shortly after Jamaica’s Independence in August 1962. Our seal of Incorporation was granted in 1970. Since its inception, the Association has grown strong in attracting members. It is recognized as the official organization representing Jamaicans in Montreal at the Federal, Provincial and Municipal levels. We are a member of the United Council for Human Rights and have accompanied delegations and presented briefs to all levels of government. Given our commitment to community development, the Jamaica Association developed our Mission Statement as follows: “To assist in improving and enhancing the quality of life for the Jamaican Community”.